Impact of Financial Distress and Accounting Conservatism - Ciptawan Ciptawan; Melina Melina (Pusat Riset dan Inovasi Nasional, 2023)
Abstract This study aims to investigate the effect of financial distress, sustainability reports, and sustainability reports on accounting conservatism. By using quantitative research methods. The data used in this study are secondary data in the form of financial reports and annual reports. The population in this study is 67 companies listed on the Indonesia Stock Exchange for the period 2020 to 2022. The sample for this study was selected using a purposive sampling technique in order to obtain 47 manufacturing companies that met the criteria. This research was conducted at manufacturing companies in the goods and consumption industry sector. In this study, the hypothesis testing method was used using Structural Equation Modeling (SEM) with the help of SmartPLS version 3.0 software.